DEVELOPMENT OF POSITIVE MOTIVATION IN FORMING AN EXISTENTIAL APPROACH AND ALTURISTIC QUALITIES IN THE PERSON IN THE MODERN WORLD (Universal International Scientific Journal, 2026)
This article is devoted to studying the role of positive motivation in the process of forming an existential approach and altruistic qualities, which play an important role in the spiritual and social development of a person in modern society. It analyzes the individual's desire to understand the meaning of life, behavior aimed at benefiting society, and the formation of a person's social activity and sense of responsibility through positive motivation. It also highlights the factors affecting the development of altruistic qualities such as the process of self-awareness of a person in the modern world, human values, and helping others.
Keywords: Existential approach; altruism; positive motivation